Rationalization of the Path Search Algorithm - Baranauskas, V.; Dervinienė, A.; Šarkauskas, K.; Bartkevičius, S. (Elektronika ir Elektrotechnika, 2010)
New algorithm, which allows organizing virtual scanner turn angle with resolution, not less than 1.29 minute, is proposed and implemented in virtual supervisory system. Implementation of new vector marks formation algorithm into supervisory system allows effectively reduce database, which is used for faster calculations of movement trajectory for any robot in any place in the environment. Usage.